Heat transfer by three types of hot pack and its implication on the flexibility of the lower back: a randomized, controlled trial - Paulina Fuentes-León; Natalia Jara-Poblete; Pía Bastías-Sánchez; Kaio Fernando Vitzel; Gabriel Nasri Marzuca-Nassr (Universidade de São Paulo, 2016)
ABSTRACT The use of hot pack is a common superficial thermotherapy strategy and one of its benefits is the increase of muscle flexibility. However, there is a lack of information about the effects of the heat pack alone, without being used in association with other therapeutic interventions, in the flexibility of the lumbar region. The aim of this study was to compare the effects generated by the application of three different pack on the flexibility of the lower backs of healthy students. Three sessions of 15 minutes of superficial heat through a hot pack (moist heat pack-MHP, seed pack-SP or gel pack-GP) were applied to the lower back. Pack and lower back temperatures and erythema were registered every 5 minutes. A Schober test was performed before the first session and after the third session. After 15 minutes of treatment, pack temperature was higher in the SP group. At the same time, lumbar temperature was lower in the GP group. The heat treatment also increased erythema in the lower back for all three groups. There was a significant increase in intragroup flexibility as assessed by the Schober Test for all groups. There are significant differences in the effect generated between the three types of pack on the flexibility of the lower back. The MHP was able to transfer more heat to the lumbar area and provided a more pronounced increase in the flexibility of lower back tissues.